Exploring metagenomic enzymes: A novel esterase useful for short-chain ester synthesis - Maester, Thaís Carvalho [UNESP]; Pereira, Mariana Rangel [UNESP]; Gibertoni Malaman, Aliandra M. [UNESP]; Borges, Janaina Pires [UNESP]; Pereira, Pâmela Aparecida Maldaner [UNESP]; Lemos, Eliana G. M. [UNESP] (MDPI, 2020)
Enzyme-mediated esterification reactions can be a promising alternative to produce esters of commercial interest, replacing conventional chemical processes. The aim of this work was to verify the potential of an esterase for ester synthesis. For that, recombinant lipolytic enzyme EST5 was purified and presented higher activity at pH 7.5, 45◦ C, with a Tm of 47◦ C. Also, the enzyme remained at least 50% active at low temperatures and exhibited broad substrate specificity toward p-nitrophenol esters with highest activity for p-nitrophenyl valerate with a Kcat /Km of 1533 s−1 mM−1. This esterase exerted great properties that make it useful for industrial applications, since EST5 remained stable in the presence of up to 10% methanol and 20% dimethyl sulfoxide. Also, preliminary studies in esterification reactions for the synthesis of methyl butyrate led to a specific activity of 127.04 U·mg−1. The enzyme showed higher esterification activity compared to other literature results, including commercial enzymes such as LIP4 and CL of Candida rugosa assayed with butyric acid and propanol which showed esterification activity of 86.5 and 15.83 U·mg−1, respectively. In conclusion, EST5 has potential for synthesis of flavor esters, providing a concept for its application in biotechnological processes.
Keywords: Esterification; Family V; Flavor esters; Lipolytic enzymes; Metagenome